Application of Trichoderma Composting Technology in the Women's Farmer Group, Sanur Kauh Village, South Denpasar District, Denpasar City, Bali Province - A.A. Sagung Putri Risa Andriani; Ni Ketut Sri Rukmini; I Gusti Ayu Dewi Seri Rejeki (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The problem being faced by farmer groups in the rainy season is the increased growth of fungi that cause plant diseases, such as Rigdiforus lignosus fungi, Fusarium oxysporum, Rizoctonia solani, Fusarium monilifome, Sclerotium rolfsii, and Sclerotium rilfisil fungi. With the concept of controlling plant-disrupting organisms (OPT) naturally, to get healthy plant cultivation free from disease (especially plant diseases caused by pathogenic fungi), Trichoderma compost (TrichoCompost Fertilizer) is applied. Interviews, face-to-face, counseling, and direct practice methods will do the method to implement this training. This activity aims to train participants to understand how to make Trichoderma compost as organic fertilizer to get healthy organic vegetables. The output target to be achieved is using appropriate technology in cow manure processing technology into compost plus Trichoderma sp. Based on the results of activities, Trichoderma compost can suppress pathogenic fungi by 98.53% so that farmer groups produce healthy plants free of pathogenic diseases.